Structural characterization and immunomodulatory activity of a novel polysaccharide from Panax notoginseng - Jiang, Xue-Lian; Ma, Gai-Fan; Zhao, Bin-Bin; Meng, Yan; Chen, Lin-Lin (Frontiers in Pharmacology, 2023)
Introduction: Polysaccharides are important components of Panax notoginseng that contribute to its immunomodulatory ability. This study aimed to isolate polysaccharides from notoginseng and investigate the structural feature and potential immunomodulatory activity. Methods: The polysaccharide was isolated from notoginseng by anion exchange and gel permeation chromatography. Its preliminary structure was characterized by Fourier transform infrared (FT-IR) spectroscopy, gas chromatography-mass spectrometry (GC-MS) and nuclear magnetic resonance (NMR) spectroscopy. The immunoregulatory function was further investigated in cyclophosphamide induced immunosuppressive mice, murine splenocytes and macrophages. Results: A novel homogeneous polysaccharide (PNPB1) was isolated from notoginseng with the molecular weight of 9.3 × 105 Da. Monosaccharide composition analysis indicated that PNPB1 consisted of Glc (88.2%), Gal (9.0%), Ara (2.4%) and trace GlcA, with the major backbone of (1→4)-linked α-Glcp, (1→6)-linked β-Glcp, and (1, 4→6)-linked β-Glcp. The polysaccharide was found to significantly enhance murine body weight, improve their thymus and spleen indices and increase the white blood cells (WBC). PNPB1 significantly enhanced splenic lymphocyte proliferation, NO and cytokine (TNF-α, IL-2, IL-10 and IFN-γ) production, as well as the phagocytosis and TLR2 expression of peritoneal macrophages, indicating potent immunoenhancement effect. Discussion: These findings provide a theoretical basis for elucidating the structure and immune activity of notoginseng polysaccharides.